From the (end of) Dōwa policies to (the start of) an anti-discrimination policy?. Issue 2 (2nd April 2020) - Neary, Ian
Abstract: There have been proposals to pass a law making discrimination against Burakumin an offence since at least 1925, but the Japanese government was never sympathetic towards them. Post-war, although some targeted measures were taken to provide improvements to Buraku communities through the Dōwa policy projects, there was still resistance to any suggestion that discrimination against Burakumin, or indeed any other group, be legally discouraged. This was despite the fact that many other liberal democracies were devising such legislation and creating commissions to hold governments to account and, at the international level, the UN was codifying human rights standards. Amos and Bondy in the following articles demonstrate how the LDP was persuaded to introduce the LPEBD into the Diet in early 2016 where it was passed with the support of all parties except for the JCP. This article sketches out the background to these developments looking at the evolution of policy across the twentieth century and the international context of its passage between 2014–2018.